Brain-Derived Neurotrophic Factor Improves Impaired Fatty Acid Oxidation Via the Activation of Adenosine Monophosphate-Activated Protein Kinase-ɑ – Proliferator-Activated Receptor-r Coactivator-1ɑ Signaling in Skeletal Muscle of Mice With Heart Failure. (January 2021) - Matsumoto, Junichi; Takada, Shingo; Furihata, Takaaki; Nambu, Hideo; Kakutani, Naoya; Maekawa, Satoshi; Mizushima, Wataru; Nakano, Ippei; Fukushima, Arata; Yokota, Takashi; Tanaka, Shinya; Handa, Haruka; et al.
Abstract : Background: We recently reported that treatment with rhBDNF (recombinant human brain-derived neurotrophic factor) improved the reduced exercise capacity of mice with heart failure (HF) after myocardial infarction (MI). Since BDNF is reported to enhance fatty acid oxidation, we herein conducted an in vivo investigation to determine whether the improvement in exercise capacity is due to the enhancement of the fatty acid oxidation of skeletal muscle via the AMPKα-PGC1α (adenosine monophosphate-activated protein kinase-ɑ–proliferator-activated receptor-r coactivator-1ɑ) axis. Methods: MI and sham operations were conducted in C57BL/6J mice. Two weeks postsurgery, we randomly divided the MI mice into groups treated with rhBDNF or vehicle for 2 weeks. AMPKα-PGC1α signaling and mitochondrial content in the skeletal muscle of the mice were evaluated by Western blotting and transmission electron microscopy. Fatty acid β-oxidation was examined by high-resolution respirometry using permeabilized muscle fiber. BDNF-knockout mice were treated with 5-aminoimidazole-4-carboxamide-1-beta-d-riboruranoside, an activator of AMPK. Results: The rhBDNF treatment significantly increased the expressions of phosphorylated AMPKα and PGC1α protein and the intermyofibrillar mitochondrial density in the MI mice. The lowered skeletal muscle mitochondrial fatty acid oxidation was significantly improved in the rhBDNF-treated MI mice. The reduced exercise capacity and mitochondrial dysfunction of the BDNF-knockout mice were improved by 5-aminoimidazole-4-carboxamide-1-beta-d-riboruranoside. Conclusions: Beneficial effects of BDNF on the exercise capacity of mice with HF are mediated through an enhancement of fatty acid oxidation via the activation of AMPKα-PGC1α in skeletal muscle. BDNF may become a therapeutic option to improve exercise capacity as an alternative or adjunct to exercise training. Abstract : Supplemental Digital Content is available in the text.